Gender incongruence in the latest International Classification of Diseases ICD-11 - Dora, Marta (Przegląd Psychologiczny, 2022)
Aim The aim of this article is to discuss the ICD-11 with respect to the changes introduced in the classification of diagnoses related to gender identity. Method The text analyses and discusses briefly the changes concerning gender identity in the new classification of diseases with respect to the content and the language as well as to their practical implications and social dimension. Results The decision by the World Health Organisation to remove transsexualism and create a new category under the name of gender incongruence in the section other than mental illnesses and disorders had been long awaited most of all by those specialising in mental and sexual health but also by patients experiencing their gender in a way different than that assigned to them at birth.